The Growth of âIslamicâ Radical Books in Indonesia - Yusuf, Choirul Fuad (Heritage of Nusantara: International Journal of Religious Literature and Heritage, 2013)
More recently, at least some decades after the triumph of global communication, thousands of fundamental and radical booksâwhether politically, religiously or culturally based booksâhave already rapidly grown in the world-wide. This phenomena, culturally can be seen from the positive spectrum as a new global dynamics of literacy civilization, but on the contrary it also can be considered as any kind of viruses treating the peaceful and harmonious life amongst Muslims community at large. Even so the growth of religious radical books, including Islamic books which are strongly influenced by the growth and distribution of any universal ideologies and philosophical thoughts. In this concern, this article attempts to explicate of how the exclusive books grew up in Indonesia. A survey on âMapping of the Islamic Books in the Post-Reformation Era in Indonesia, earned out in 2013 showed us, besides there is an increase of the practical books on Islam read by Muslims at large, the exclusive and extreme books have been growing significantlyâincluding the books published by both fundatnental and radical book publication.